O efeito de um sinal sobre o repertorio comportamental do rato - Ades, César; Oliveira Bueno, José Lino (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Stimuli that are followed by reinforcement are reported to increase general activity in the rat. In order to study more precisely this effect, rats were observed in two training situations: the experimental group (n — 4) was subjected to paired presentations of a 15 seconds tone and water; in the control group (n = 3), tone and reinforce were not presented contiguously